PENGEMBANGAN MATERI AJAR DENGAN TEMA “WOHNUNG” PADA E-PORTOFOLIO WEB BERBASIS GOOGLE.SITES UNTUK KETERAMPILAN MEMBACA SISWA KELAS XI SEMESTER 2 BAHASA JERMAN - AZHARY DINAHUSARY; Dra. Fahmi Wahyuningsih, M.Pd (LATERNE, 2025)
Increased German language learning is increasingly in demand in Indonesia, especially by students. With the application of German language learning in various schools, it is important to understand language empathy skills which include listening, speaking, reading, and writing. The formulation of the problems of this study are 1. How is the development of teaching materials on the theme of wohnung on the e-portfolio website for German reading skills? How is the feasibility of E-portfolio web media with the theme “Wohnung” on the e-portfolio website based on media experts and material experts? This research aims to develop teaching materials on the theme ‘wohnung’ in e-portfolio format that focuses on reading skills. The method used is Research and Development to create and test the effectiveness of the product. It is hopefully that the results of this study can inspire other researchers to apply it directly to students. Keywords: German Language Learning, E-Portfolio, Research and Development